Integrated Smart Rescue Box Design With Information Systems as a Solution to Indonesian Disaster Emergency Response - Supriadi, Dewi Sri Mulyana; Jaya, Hendra; Djawat, Yasser Abd; Parenreng, Jumadi Mabe (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
This study uses the design method with a prototype research model. This is motivated by the fact that Indonesia is prone to natural disasters, so preparing for an effective and efficient disaster emergency response process is necessary. The resulting innovation is an intelligent rescue box prototype product integrated with an information system as a disaster emergency response solution, especially in meeting the basic emergency needs of post-disaster refugees. The effect will consist of two, and the first is the Smart rescue box (SRB), which provides the emergency needs of evacuees in one package to meet the electricity needs of refugees. There is a solar tracker system with real-time clock (RTC) data that is set as if it can follow the direction of the sun's movement for maximum absorption of sunlight. The second product is the SRB information system which is a disaster information system consisting of several useful features and a disaster education menu that can provide insights regarding disasters and disaster information that can be accessed easily. The measurement and observation test results show that the product has worked as expected, so it is feasible. The resulting product is still in the form of a prototype so that suggestions for further research can be further developed in terms of features and technology to become a complete product to facilitate the disaster emergency response process.